Computational analysis of the commonality among trajectories - Brito e Abreu, F. (Seminário de encerramento do Projeto Gesto, 2015)
Computing the commonality among trajectories requires the ability to measure the distance between each pair of them. Once you solve the previous problem, then we can choose as a surrogate of that commonality the trajectory that minimizes the distance to all the other trajectories. We will call it the mean trajectory. To solve the first problem we will present proposals from Topology, Speech Recognition and Computational Biology.